Perancangan dan Pembuatan Sistem Informasi Penilaian Pada SMA Negeri 14 Medan - Marthin Yohannes Simanjuntak (Jurnal Multidisiplin Indonesia, 2023)
Vocational High School of Gajah Tunggal Metro City is one of the schools located in Metro that utilizes social media and websites in sharing information. Nevertheless, the results of an interview with a teacher at Vocational High School of Gajah Tunggal Metro City, Mr. Andre Rusdiono A.Md as the head of the Computer Network Engineering department stated that the information provided on the website was incomplete and not up-to-date. Information such as new student registration was shared through Instagram and Facebook as well as announcements for new student admissions were still shared by posting them on the bulletin board. In this case, the researcher designed a website-based information system using Laravel framework with a development method, namely SDLC (System Development Lift Cycle) and a testing technique, namely the Black Box Testing technique. This development was conducted to aid staff in managing school data and reaching wider community in school promotion activities.